Knowledge of breast cancer and breast self-examination practice among Yemeni female school teachers in Malaysia - Noman, Sarah Noman Abdulrahman; Abdul Rahman, Hejar; Akhtari-Zavare, Mehrnoosh; Al-Wajeeh, Nahla Saeed; Kadir @ Shahar, Hayati; Ismail, Suriani (2017)
Background: Breast cancer is the most frequent cancer and the second cause of cancer deaths among women worldwide, including Yemeni women. The purpose of this study is to determine knowledge on breast cancer and breast self-examination (BSE) practice among Yemeni female school teachers in Klang Valley, Malaysia. Methodology: A cross-sectional study was conducted among 163 Yemeni female schoolteachers in Malaysia between April 2017- May 2017. The inclusion criteria for this study are teachers who were teaching at the selected primary and secondary Arabic schools, aged 20 years old age and above, and teachers who signed consent form to participate in the study. Teachers who had a previous history of breast cancer or who were pregnant or lactating were excluded from the study. A simple random sampling method was utilized and data were collected via self-administered questionnaire by using a validated questionnaire, which was developed for this study. The questionnaire consisted of four sections, background information of respondents, knowledge on breast cancer, health belief model, practices related to breast cancer screening. Result: The response rate derived in this study was100 %. The mean age of respondents was 32.8 ±7.23 years, 128(78%) of them were married, 26 (15.9%) had family history of breast cancer and 34 (20.9%) of them previously participated in breast cancer education program. The majority of respondents 131(79.9%) had heard/read about breast cancer screening, but only 43(26.2%) practiced breast self-examination and 136(82.9%) had intention to practice BSE in the future. This study showed majority of respondents 121(74.2%) and 104(63.8%) had low level of knowledge on breast cancer and BSE practice, respectively. Univariate analysis showed that hear/read about breast cancer screening, participated in breast cancer education programs, were statistically associated with knowledge of breast cancer (p=0.001) (p=0.005) respectively, Also, hear/read about breast cancer screening (p=0.01), participated in breast cancer education program (p=0.003), and education level (p=0.01), were statistically associated with BSE practice. Conclusions: The findings showed that knowledge of Yemeni female school teachers towards breast cancer and rate of BSE practice are low. Targeted education should be implemented to improve knowledge of breast cancer and BSE practice to improve breast cancer prevention among this group.